Subcutaneous administration of benzathine benzylpenicillin G has favourable pharmacokinetic characteristics for the prevention of rheumatic heart disease compared with intramuscular injection: A randomized, crossover, population pharmacokinetic study in healthy adult volunteers - Kado, J.H.; Salman, S.; Henderson, R.; Hand, R.; Wyber, R.; Page-Sharp, Madhu; Batty, Kevin; Carapetis, J.; Manning, L. (OXFORD UNIV PRESS, 2020)
Background: Benzathine penicillin G has been used as monthly deep intramuscular (IM) injections since the 1950s for secondary prevention of acute rheumatic fever and rheumatic heart disease (RHD). Injection frequency and pain are major programmatic barriers for adherence, prompting calls for development of better long-Acting penicillin preparations to prevent RHD. We hypothesized that subcutaneous (SC) administration of benzathine penicillin G could delay penicillin absorption when compared with IMinjections.